Application of the Guided Discovery Learning Model to Improve Class IV Science Learning Outcomes at SD Negeri Mulyosari - Sulistyorini, Dyah (Universitas Sebelas Maret, 2022)
This study aims to improve learning outcomes in science subjects by applying the guided discovery learning model to fourth grade students at SD Negeri Mulyosari. The research conducted was Classroom Action Research (PTK) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing, and reflecting. In the pre-cycle of students who completed after carrying out the post test as much as 25%. In cycle I, students who complete increased by 70%. In cycle II, the students who passed increased again to 85%. These results indicate that the guided discovery learning model can improve student learning outcomes grade IV science at SD Negeri Mulyosari.